OODA Loops: Concept of Resilience Analysis and Strategic Management of MSME Development During the Covid-19 Pandemic in East Java Province - Fahmid; Achmad Syaugi (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2021)
The Covid-19 pandemic that occurred in the community has resulted in crises in several economic sectors. In the global economy, the Covid-19 pandemic has had a very significant impact on the domestic economy. This can be seen in East Java's economic growth, which only increased by 3.04% in the quarter I, far from the 5% average in the same period. This condition also has an impact on the Micro, Small and Medium Enterprise (MSMEs) sector in East Java Province. In recent years, MSMEs growth in 2016-2019 has increased by 4.2% and the average contribution of MSMEs to East Java's Gross Domestic Product (GDP) is 50% within 3 years. For this reason, research is needed to explore and analyze the condition of MSMEs in East Java so that they can determine the decisions made by MSMEs business actors in East Java in maintaining their business during the Covid-19 pandemic. In this study, an analysis using the OODA loops approach was used as a benchmark. efforts or defense measures for MSMEs business actors in East Java. In collecting data, this study conducted an online survey of MSMEs in East Java to several business sectors using non-probability sampling. From the results of this survey, as many as 96% of business actors claimed to have experienced the negative impact of Covid-19 on their business processes. Then as many as 75% of them experienced the impact of a significant decline in sales and only 13% of business people believe they have a crisis management plan and find solutions to maintain their business. Therefore, it is recommended that every MSMEs business actor in East Java use the OODA loops concept as a problem solver in dealing with economic crisis principles due to the Covid-19 pandemic.